Electric Vehicle Adoption in Jabodetabek: The Impact of Infrastructure, Cost, and Perceived Value - Jusuf, Eddy; Sunitiyoso, Yos (Jurnal Samudra Ekonomi dan Bisnis, 2026)
This research investigates the primary factors affecting consumers’ intention to adopt electric vehicles (EVs) in the Jabodetabek region of Indonesia. This research analyzed data from 188 participants using a quantitative method through PLS-SEM. The model integrates the Theory of Planned Behavior (TPB), the Perceived Value (PERVAL) framework, and several contextual factors. The results show that perceived quality and price value significantly affect attitudes, while charging station availability and resale value directly influence adoption intention. Interestingly, attitude, subjective norms, and perceived behavioral control were not significant predictors. The findings suggest that in emerging markets, practical and economic concerns outweigh psychological or emotional drivers. These insights offer guidance for policymakers and businesses to focus on infrastructure development and value-enhancing strategies to accelerate EV adoption.